CORPORATE FINANCIAL DISTRESS – CORPORATE DEBT RESTRUCTURING MECHANISM IN INDIA - Rao, Kambakula Appa; Jessica, V. Mary (PEOPLE: International Journal of Social Sciences, 2017)
After Recession, corporate was not doing well. There is a situation where the company’s cash flow is not enough to pay financial obligation is called Corporate Financial Distress. External and internal factors of an environment are causes for corporate financial distress. The main objective of this paper is to know the causes for financial distress. This study finds that Delay in obtaining permissions, Short term funds used for long term purpose, Slowdown in Economy and Investments are diverted into other projects most important factors for the financial distress of companies. In this situation, Corporate Debt Restructuring Mechanism is a platform for corporate to stop winding up and come out from financial distress. This study finds that 97 out of 530 companies exited successfully come out from CDR Mechanism.